Cross‐genera transferable e‐microsatellite markers for 12 genera of the Lamiaceae family. (12th December 2012) - Karaca, Mehmet; Ince, Ayse Gul; Aydin, Adnan; Ay, Saadet T
Abstract Background The Lamiaceae family contains many high‐valued medicinal, aromatic and ornamental plant species. Several members of the genera in this family are under heavy pressure of collection for commercial use. DNA markers such as microsatellites could be used to identify commercially important genotypes and to select high‐yielding ones for development of new varieties. Results A total of 12 432 expressed sequence tags (ESTs) from Salvia fruticosa, S. miltiorrhiza, S. sclarea and Stenogyne rugosa were analyzed. A total of 6216 ESTs were found to be unique according the redundancy test used. Results of this study indicated that the use of redundant ESTs in comparison to non‐redundant ESTs was advantageous in terms of higher cross‐genera transferability of the markers. A total of 75 EST–microsatellite primer pairs were tested using two different polymerase chain reaction amplification profiles and 52 were found to be cross‐genera transferable. Cross‐genera transferability of the e‐microsatellite primer pairs varied from one species to 12 species tested. It was noted that cross‐genera transferability of e‐microsatellite primer pairs decreased as the evolutionary distance between the sources and target species increased. Conclusion This study indicated that EST resources from Salvia spp. and Stenogyne rugosa could be successfully used to identify cross‐genera transferable e‐microsatellite markers for uncharacterized genomes of the genera in the Lamiaceae family. These e‐microsatellite markers could allow one to perform comparative analyses of population structure and genomic studies, and facilitate comparative linkage mapping in the genera studied. E‐microsatellite primer pairs reported in this manuscript are equivalent to a total of 135 e‐microsatellite primer pairs since many e‐microsatellite primer pairs show cross‐genera transferability. © 2012 Society of Chemical Industry